2013
DOI: 10.1093/ndt/gft020
|View full text |Cite
|
Sign up to set email alerts
|

A new recombinant MnSOD prevents the Cyclosporine A-induced renal impairment

Abstract: Administration of rMnSOD prevents CsA-mediated impairment of the GFR along with morphological alteration. This effect could be related to the inhibition of ROS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 22 publications
5
28
0
Order By: Relevance
“… 49 , 50 Previous studies established that ROS production and oxidative stress are involved in CsA nephrotoxicity. 35 , 46 , 51 This study supported our hypothesis that SCE had renal protective effects in CsA nephrotoxicity model, a well-established renal injury model. In this model, CsA-induced generation of ROS led to an increase in the expression of 4-HNE (a product of lipid peroxidation) and HO-1 (an inducible isoform in response to oxidative stress).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“… 49 , 50 Previous studies established that ROS production and oxidative stress are involved in CsA nephrotoxicity. 35 , 46 , 51 This study supported our hypothesis that SCE had renal protective effects in CsA nephrotoxicity model, a well-established renal injury model. In this model, CsA-induced generation of ROS led to an increase in the expression of 4-HNE (a product of lipid peroxidation) and HO-1 (an inducible isoform in response to oxidative stress).…”
Section: Discussionsupporting
confidence: 84%
“…Numerous studies have demonstrated that the CsA-induced nephrotoxicity, which is characterized by decreased glomerular filtration rate and fibrosis, is a major cause of chronic renal disease in rat models and this can be applied to clinical practice as well. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Inulin clearance was performed as previously described [ 18 ]. Briefly, mice were anesthetized with Inactin (Sigma) 100 mg/kgBW, tracheostomized, placed on a surgical table.…”
Section: Methodsmentioning
confidence: 99%
“…mesangial function) contributions [ 31 , 32 ]. Several factors, such as reactive oxygen species, may functionally modulate the GFR [ 33 ]. The data on urinary volume and urinary sodium are in keeping with the well-known effects of AVP on diuresis and urinary sodium excretion, as well as with the data from four patients with CDI studied by Hanouna et al .…”
Section: Discussionmentioning
confidence: 99%